Ga10[Si(SiMe3)3]6, [Ga10(SitBu3)6]-, and [Ga13(SitBu3)6]: syntheses and structural characterization of novel Gallium cluster compounds - Kehrwald, Michael; Köstler, Wolfgang; Rodig, Alexander; Linti, Gerald W.; Blank, Thomas; Wiberg, Nils (Organometallics, 2001)
Ga10[Si(SiMe3)3]6, [Ga10(SitBu3)6]-, and [Ga13(SitBu3)6]-Syntheses and Structural Characterization of Novel Gallium Cluster Compounds†